2022
DOI: 10.1007/s00268-021-06420-w
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia in the Initial Management of Acute Pancreatitis: A Systematic Review and Meta‐Analysis of Randomised Controlled Trials

Abstract: Background The optimal analgesic strategy for patients with acute pancreatitis (AP) remains unknown. Objective The present systematic review and meta-analysis aims to compare the efficacy of different analgesic modalities trialled in AP. Methods A systematic search of PubMed, MEDLINE, EMBASE, CENTRAL, SCOPUS and Web of Science conducted up until June 2021, identified all randomised control trials (RCTs) comparing analgesic modalities in AP. A pooled analysis was undertaken of the improvement in pain scores as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Abdominal pain can be profound in acute pancreatitis, and for most patients, strong opioid analgesia is appropriate, reducing the need for supplementary analgesia over other regimens; analgesia ladders can be used for those with less severe pain, mindful that early and effective relief is a priority [174]. NSAIDs are an opiate-sparing alternative for uncomplicated disease [175], but run the risk of renal injury in more severe disease. Experimental evidence indicates opiates increase sphincter of Oddi phasic contractions that may increase pressure within the bile duct [176], but randomised trials have demonstrated that opiates are as, if not more, effective than alternatives, and as safe in acute pancreatitis [177].…”
Section: Pain Managementmentioning
confidence: 99%
“…Abdominal pain can be profound in acute pancreatitis, and for most patients, strong opioid analgesia is appropriate, reducing the need for supplementary analgesia over other regimens; analgesia ladders can be used for those with less severe pain, mindful that early and effective relief is a priority [174]. NSAIDs are an opiate-sparing alternative for uncomplicated disease [175], but run the risk of renal injury in more severe disease. Experimental evidence indicates opiates increase sphincter of Oddi phasic contractions that may increase pressure within the bile duct [176], but randomised trials have demonstrated that opiates are as, if not more, effective than alternatives, and as safe in acute pancreatitis [177].…”
Section: Pain Managementmentioning
confidence: 99%
“…In the early phase of AP, pain is ubiquitous, caused by the release of inflammatory mediators, arachidonic acid metabolites, bradykinins, and proteases, all of which may stimulate primary afferent sensory neurons. 27 Adequate analgesia is essential to AP patient management 28 and may reduce systemic inflammation. The MED score of the original PASS did not define a maximal upper limit, while the other four components have defined ranges, which may skew the composite PASS.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, pain management is cornered on the use of opiates although nowadays a multimodal approach paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs), metamizole, opiates, ketamine and epidural analgesia is commonly used. Two recent meta-analyses have appeared, identifying 6 and 12 RCTs, respectively [16,17]. Both meta-analyses indicate that NSAIDs and opiates are equally effective, but a substantial paucity of data exists.…”
Section: Pain Managementmentioning
confidence: 99%